Posisi Turning Point USA sebagai Civil Society Sayap Kanan dalam Demokrasi Amerika Serikat - Yilmaz Omar Sebastian; Lyndia Aziza Shafarosa; Muradi Muradi (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the position of Turning Point USA (TPUSA) as a right-wing civil society organization in the context of American democracy and examines how it influences contemporary political dynamics through ideological mobilization. Since its establishment in 2012 by Charlie Kirk, TPUSA has rapidly developed as a conservative movement targeting youth political engagement through educational institutions, social media activism, and political campaigning. This research employs a library research method with a discourse analysis approach to examine TPUSA’s narrative construction, communication strategies, and political agenda. Philippe Schmitter’s civil society theory is used to explain TPUSA’s role as a non-state actor, while Muthiah Alagappa’s theoretical perspective highlights the ambivalent nature of civil society, which can either strengthen or undermine democracy. The findings show that TPUSA promotes conservative ideology while operating as an extension of partisan political interests closely connected to the Republican Party and Donald Trump’s political network. Beyond advocacy and political education, TPUSA contributes to political polarization, delegitimization of democratic institutions, and the spread of disinformation, most evidently through its involvement in the “Stop the Steal” movement. This study concludes that civil society organizations may become instruments of democratic backsliding when driven by ideological exclusivity and partisan motives.